OVERCOMING THE “RESOURCE CURSE”: WELFARE POLICY AND CIVIL CONFLICT IN RENTIER STATES - Mukasheva, Zhamilya (Nazarbayev University School of Sciences and Humanities, 2017)
Existing literature cannot explain why some rentier states, that is, states dependent on revenues from exports of natural resources or foreign aid, experience significantly more civil conflicts while others remain peaceful. The first part of this thesis seeks to explain this puzzle by examining the role of government policies. In particular, I argue that rentier states that invest a lot in welfare policy are better able to prevent civil conflict because high welfare spending contributes to a better institution quality, which in turn reduces uncertainty or information asymmetry between the rentier government and rebels. Using data on rentier states from 1980 to 2015, I find that higher welfare spending reduces risk of a civil conflict in rentier states.
"РЕСУРСТАР КАРҒЫСЫНАН" АЙРЫЛУ: РАНТЬЕ МЕМЛЕКЕТТЕРІНДЕГІ ӘЛЕУМЕТТІК САЯСАТ ЖӘНЕ АЗАМАТТЫҚ ҚАҚТЫҒЫС
ПРЕОДОЛЕНИЕ «ПРОКЛЯТИЯ РЕСУРСОВ»: СОЦИАЛЬНАЯ ПОЛИТИКА И ГРАЖДАНСКИЙ КОНФЛИКТ В ГОСУДАРСТВАХ-РАНТЬЕ
Keywords: civil conflict; әлеуметтік саясат; азаматтық қақтығыс; welfare policy; социальная политика; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science